Evaluation of the Flexural Stress and Deflection in a Rigid Pavement Utilising Finite Element Analysis - Nadheer Albayati (Journal of Studies in Civil Engineering, 2025)
The rigid pavement is manufactured from cement concrete, enabling it to withstand heavy truckloads throughout its service life. The configuration, location, and wheel weight all affect the flexural stresses and deflections that influence pavement deterioration, which in turn impacts pavement life and user safety. The paper investigates the value and position of critical flexural stress and deformations under the tires of a whole moving truck axle. A multi-trailer truck weighing 66 tons crosses an undoweled concrete panel measuring 3.75 m in width and 6 m in length. Four moving truck paths are analyzed to determine the maximum critical flexural stress and deflection by finite element theory utilizing the SAP2000 software. The findings showed that the wheel's location relative to the panel edge is a significant factor in generating stresses and deflection. The maximum stress of 2.89 MPa occurs on the longitudinal edge of the panel, and the maximum deflection of 4.1 mm occurs on the panel corner. It is not necessary that packing many axles on a single panel surface leads to maximum stress. The corner area is the most problematic position because it exhibits the maximum deflection under all axle types.